POLITIK PENDIDIKAN DI INDONESIA DAN ISU PENYELENGGARAAN PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA - Noviana Diswantika; Iip Istirahayu; Agus Taufiq (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2022)
This article aims to describe the political issues of education that occur in Indonesia. The study of issues from the perspective of the importance of education to the dynamics of education in Indonesia, one of which changes the curriculum from year to year until now has not found the right formulation. Until now, the Independent Learning Campus Teaching (MBKM) policy is seen as the right formula, but it is still faced with fatal weaknesses that result in curriculum adaptation in each study program with adjustments to the policy. Solutions and recommendations regarding the political condition of education in Indonesia and the issue of MBKM will be discussed further.